Quantum information storage and state transfer based on spin systems - Song, Z.; Sun, C.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The idea of quantum state storage is generalized to describe the coherent transfer of quantum information through a coherent data bus. In this universal framework, we comprehensively review our recent systematical investigations to explore the possibility of implementing the physical processesof quantum information storage and state transfer by using quantum spin systems, which may be an isotropic antiferromagnetic spin ladder system or a ferromagnetic Heisenberg spinchain. Our studies emphasize the physical mechanisms and the fundamental problems behind thevarious protocols for the storage and transfer of quantum information in solid state systems.